REINSTATING FOR ENTREPRENEUR TERMINOLOGY IN MANAGEMENT, AN ALTERNATIVE OF CRITICAL DISCOURSE - Oscarius Yudhi Ari Wijaya (JURNAL MANAJEMEN DAN BISNIS, 2022)
Academic scientific culture has encouraged the birth of many new ideas, both in the form of new theoretical conceptions and modeling of a research, including several new ideas. which gave birth to new terms in a scientific field, including the field of management, including the term "entrepreneur" or its derivatives such as "entrepreneurship" or "entrepreneurial". The purpose of this article is to conduct a critical study regarding the appropriateness of the use or development of these terms. A new approach that integrates analysis of semantic, conceptual-theoretical and cognitive perspectives is used to confirm their findings, where it is known that new findings are confusing, overlapping, and useless. 146/U/2004 is called chaos, ambiguity, and misunderstanding. Other new findings in this article are in the analytical methods used, namely semantics, conceptual-theoretical and cognitive and the results of the discussion in this paper suggest a way that can improve the deepening study of management concepts rather than building terminology that can lead to confusion, overlap and redundancy. , misunderstanding, superficiality and imperfection of the concept.